2016
DOI: 10.3109/09513590.2016.1161743
|View full text |Cite
|
Sign up to set email alerts
|

Drospirenone as estrogen-free pill and hemostasis: coagulatory study results comparing a novel 4 mg formulation in a 24 + 4 cycle with desogestrel 75 μg per day

Abstract: DRSP 4 mg was not associated with any meaningful changes on hemostatic parameters, indicating a lack of effect on hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 13 publications
4
28
0
6
Order By: Relevance
“…These data agree with the neutral effects of 4 mg drospirenone on haemostatic variables reported in a long-term study [21]. Thus, 4 mg drospirenone may be considered a safe contraceptive option that may be used in women with a thromboembolic risk factor, without increasing the risk of a venous or arterial thromboembolic event.…”
Section: Safetysupporting
confidence: 88%
See 2 more Smart Citations
“…These data agree with the neutral effects of 4 mg drospirenone on haemostatic variables reported in a long-term study [21]. Thus, 4 mg drospirenone may be considered a safe contraceptive option that may be used in women with a thromboembolic risk factor, without increasing the risk of a venous or arterial thromboembolic event.…”
Section: Safetysupporting
confidence: 88%
“…The study comprised 39 women who took the 4 mg drospirenone POP (24/4) and 29 women who took desogestrel 75 lg daily for nine continuous cycles. The haemostatic variables evaluated were activated protein C resistance, antithrombin III, D-dimer, C-reactive protein and coagulation factors VII and VIII [21]. The study results showed that 4 mg drospirenone did not influence the haemostatic variables and did not affect the balance between procoagulant and anticoagulant factors.…”
Section: Safetymentioning
confidence: 88%
See 1 more Smart Citation
“…This is induced by the action of ethinylestradiol on hepatic and vascular function and is documented by the rise of sex hormone‐binding globule (SHBG) . Progestogens with pronounced androgenic properties, eg levonorgestrel, may counteract estrogen‐induced changes in the hepatic synthesis of hematological factors; other progestogens with antiandrogenic properties or with neutral androgenetic properties may not …”
Section: Discussionmentioning
confidence: 99%
“…Следовательно, он может противодействовать стимуляции коагуляции, вызванной активацией РААС. Дроспиренон в отсутствие эстрогена уменьшает активность коагуляцииснижает уровни фактора VII и D-димера [36]. Однако в комбинации с эстрогеном он повышает риск ВТЭ [37].…”
Section: влияние гестагенов на параметры коагуляцииunclassified